HALAL CERTIFICATION SYSTEM AS A KEY DETERMINANT OF FIRM INTERNATIONALISATION IN THE PHILIPPINES AND MALAYSIA - François N. Dubé,; Yang HaiJuan,; Huang Lijun, (Asian Academy of Management Journal, 2016)
There is a broad consensus to the effect that public agencies can mitigate the obstacles and uncertainties associated with the process of firm internationalisation. One critical aspect of such interventionist policy is the establishment of a national/region halal certification system, which has been widely recognised as core factor in the international expansion of halal food firms. Based on a thorough field research conducted in the halal food industries of the Philippines and Malaysia, the present article shall explicitly examine how exactly different models of halal certification can promote and ease access of local firms to international markets. Using both qualitative and quantitative methodologies, the present article will allow us to formulate general conclusions regarding the relationship between firm internationalisation and halal certification, as well as specific insights for other halal food industries seeking to promote their international activities.